ANALISIS DAMPAK JUDI ONLINE TERHADAP KESEJAHTERAAN MASYARAKAT KECAMATAN PAITON DALAM PERSPEKTIF MAQASHID SYARIAH - Himmah, Mufidatul; Rizkillah, Moch. (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the impact of online gambling on societal welfare through the lens of Maqashid Syariah, focusing on the principle of wealth protection (Hifz al-Mal). As a negative consequence of technological advancement, online gambling has become widespread in Indonesia, leading to significant economic, social, and moral issues. This research employs a qualitative, descriptive-analytical approach conducted in Paiton District, Probolinggo Regency. Data were gathered through in-depth interviews, observations, and literature review, and analyzed inductively to identify the real impact of online gambling on community well-being. Utilizing the Maqashid Syariah framework, the study highlights wealth protection and also explores its effects on life (Hifz an-Nafs), intellect (Hifz al-Aql), lineage (Hifz an-Nasl), and religion (Hifz ad-Din). The findings indicate that online gambling directly contributes to worsening household economic conditions, increased psychological stress, and a decline in spiritual life within the community. The study aims to provide comprehensive insights into how online gambling contradicts Islamic values and harms societal welfare. It also seeks to contribute to the development of more effective Islamic economic policies to protect communities from the negative impacts of online gambling.